A retrospective study on the effects of exclusive donor human milk feeding in a short period after birth on morbidity and growth of preterm infants during hospitalization. Issue 35 (September 2017) - Kim, Eun Jeong; Lee, Na Mi; Chung, Sung-Hoon
Abstract : Abstract: The risks and benefits of feeding preterm formula (PF) versus donor human milk (DHM) in preterm infants are uncertain, and studies evaluating the efficacy of DHM to the morbidities and growth of preterm infants in the neonatal intensive care unit are confused by the need for milk fortification. We aimed to determine and compare the outcome of short-term morbidities in neonatal intensive care unit and growth between premature infants fed exclusively DHM only until a volume of 130 mL/kg/d of enteral feeding was achieved and infants fed with a PF mix after birth. The data of 132 infants with low birth weight of <1500 g and gestational age of less than 32 weeks were considered. Ninety infants were analyzed, of which 86 were discharged alive. The DHM group (n = 36) was made up of infants who were fed exclusively with DHM, whereas the PF group (n = 54) consisted of infants who were fed with a combination of PF and either DHM or human milk, until a volume of 130 mL/kg/d of enteral feeding was achieved. Once feeding in the DHM group progressed to volumes greater than 130 mL/kg/d, infants were fed fortified DHM and PF alternately. One infant (2.8%) in the DHM group had late-onset sepsis or necrotizing enterocolitis compared with 21 (38.9%) in the PF group (adjusted odds ratio 0.05, 95% confidence interval 0.01–0.41); 13 (36.1%) infants in the DHM group had bronchopulmonary dysplasia compared with 38 (70.4%) in the PF group (odds ratio 0.18, 95% confidence interval 0.05–0.41). Although the DHM group demonstrated a comparatively lower rate of weight gain, head circumference increment, and height increment from birth to the age at which an enteral feeding volume of 130 mL/kg/d was achieved, there were no significant differences in these values at 36 weeks' postmenstrual age between both groups.